Editorial: Advanced Learning Technologies, Performance Technologies, Open Contents, and Standards - Some Papers from the Best Papers of the Conference ICCE C3 2009 - Fanny Klett (IEEE Fellow); Kiyoshi Nakabayashi; Stephen J.H. Yang (Knowledge Management & E-Learning: An International Journal, 2010)
This special issue deals with several cutting edge research outcomes from recent advancement of learning technologies. Advanced learning technologies are the composition of various related technologies and concepts such as i) internet technologies and mobile technologies, ii) human and organizational performance/knowledge management, and iii) underlying trends toward open technology, open content and open education. This editorial note describes the overview of these topics related to the advanced learning technologies to provide the common framework for the accepted papers in this special issue.